2012
DOI: 10.1134/s1023193512030044
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on platinum single-crystal electrodes

Abstract: This work reviews three different approaches for the study of temperature effects on the platinum single crystal | solution interphase. First, the method of analysis of temperature dependent voltammetric data with the help of a generalized isotherm is described and illustrated for the case of adsorbed hydrogen and OH species on Pt(111) in 0.1 M HClO 4 . This method of analysis allows a detailed evaluation of the thermo dynamic data of charge transfer adsorbed species, namely, the standard molar Gibbs energy, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 41 publications
2
24
1
Order By: Relevance
“…Later, works employing more precise methods to characterize the interface, like the analysis based on the electrocapillary equation [20,21,24], reported a good agreement with results from the generalized isotherm strategy [15,17].…”
Section: Introductionsupporting
confidence: 50%
See 2 more Smart Citations
“…Later, works employing more precise methods to characterize the interface, like the analysis based on the electrocapillary equation [20,21,24], reported a good agreement with results from the generalized isotherm strategy [15,17].…”
Section: Introductionsupporting
confidence: 50%
“…Commonly, they have been attributed to Hads on step sites [11,12,14], because peak potentials are constant and charge densities linearly increase with step density, in good agreement with a process where one electron is exchanged per step atom [11][12][13][14]. However, because of their unusual pHdependent shift of 50 mV NHE/pH unit [22,33], and their sharp shape, which can be only modeled by assuming net attractive interactions between adsorbed species [30] in contrast to repulsive Hads lateral interactions on {111} terraces [15,17,20,24], it has been recently also suggested that these peaks at 0.13V and 0.28 V could be caused by competitive co-adsorption of OHads, or even adsorbed oxygen, Oads, from water dissociation at steps, through a more complex reaction scheme [33]:…”
Section: Cvs Inmentioning
confidence: 93%
See 1 more Smart Citation
“…For the different experiments, the reference electrode was kept at room temperature (298 K). To transform the direct potential reading to the RHE scale at 298 K values, the direct potential reading should be corrected for the thermodiffusion potential using the procedure explained in reference [21]. Solutions were prepared from sulfuric acid, perchloric acid, sodium perchlorate, formic acid (Merck suprapur in all cases) and ultrapure water from Elga.…”
Section: Methodsmentioning
confidence: 99%
“…Larger differences are observed on the Pt(111) electrode, for which, a diminution of the activation energy is observed around 0.6 V in sulfuric acid solutions. The diminution should be then related to the changes in the sulfate coverage, since, in this region the sulfate layer rearranges to reach the maximum coverage [21].…”
Section: Activation Energy For the Reaction Through The Active Intermmentioning
confidence: 99%